Specialization in Nursing from the Perspective of Academician, Clinician and Student Nurses: A Qualitative Research - Gizem Deniz Büyüksoy; Ayla Ünsal; Gamze Saatçi (Atatürk University, 2024)
Objective: The health care needs in the community make the specialization in nursing more crucial. The aim of this study is to examine the views of academicians, clinicians and student nurses towards specialization in nursing. Methods: This qualitative type of study was conducted in the case study design. The study was carried out between October and November, 2021, with 21 participants selected by the maximum diversity sampling technique. The semi-structured interview technique was used and the expressions were recorded. The theme and subtheme were determined by the content analysis. The Standards for Reporting Qualitative Research (COREQ) was used to report this research. Results: Three main themes and six sub-themes were determined. The main themes were quality of care, obstacles and constructive ideas. The sub-themes were clinical knowledge and skills, scientific attitude, education system, institutional factors, change in policies and dignity. Conclusion: The participants have faith in the fact that specialization in nursing would increase the quality of health care and nursing. They believed that the health care system and working conditions prevent specialization. They emphasize the need to develop policies for the betterment of specialization.